2016
DOI: 10.18052/www.scipress.com/ilshs.70.21
|View full text |Cite
|
Sign up to set email alerts
|

The Burnout Level of Call Center Agents in Metro Manila, Philippines

Abstract: Abstract. The aim of this study was to measure the exhaustion, cynicism and professional efficacy that would determine an individual's level of burnout. A convenient sample of employees (N=747) was obtained from different call centers in Metro Manila. The results indicated a high level of exhaustion for the age group of 18-29 years old and for the female respondents. More than half of the respondents were high in cynicism and those who reported a low professional efficacy were mostly females. Age showed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…One factor is the social demographic status of employees. It is age-related that younger employees tend to be more prone to burnout because in younger employees their lack of experience in handling excessive job requests or overcoming customer difficulties or anger (Montalbo, 2016). This has similarities with research conducted by Drissi et al (2021), that age factor has a role in the occurrence of burnout.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…One factor is the social demographic status of employees. It is age-related that younger employees tend to be more prone to burnout because in younger employees their lack of experience in handling excessive job requests or overcoming customer difficulties or anger (Montalbo, 2016). This has similarities with research conducted by Drissi et al (2021), that age factor has a role in the occurrence of burnout.…”
Section: Resultsmentioning
confidence: 56%
“…In this study it is proven that when the workload increases and the demands of work are high, employees tend to feel tired increases. While in research conducted by Montalbo (2016), it was found that there are differences in responsibility, in this case related to the level of management has a significant relationship. This means that the more an employee in an organization, it will be more susceptible to burnout.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The common symptoms include excessive sleepiness or absence of energy. When individuals encounter burnout, they are frequently experienced weariness since this is the clearest sign of burnout (Montalbo, 2016). Call centers emphasize a unique environment where emotional labor demands can be high and limited autonomy.…”
Section: Burnout Conditionsmentioning
confidence: 99%